Six‐Step Continuous Flow Synthesis of Diclofenac Sodium via Cascade Etherification/Smiles Rearrangement Strategy: Tackling the Issues of Batch Processing. Issue 45 (23rd June 2022) - Wang, Lulu; Liu, Minjie; Jiang, Meifen; Wan, Li; Li, Weijian; Cheng, Dang; Chen, Fener
Abstract: Diclofenac sodium is a widely used nonsteroidal anti‐inflammatory drug (NSAID) as over‐the‐counter (OTC) medication for the treatment of inflammatory diseases. Herein, the development of an intensified six‐step continuous flow synthesis of diclofenac sodium from commercially available aniline and chloroacetic acid is described. A challenging and unprecedented etherification/Smiles rearrangement cascade of 2‐chloro‐ N ‐phenylacetamide and 2, 6‐dichlorophenol into hydroxyacetyldiphenylamine operated with the precise control of reaction conditions in continuous flow was realized as the key step in this multistep synthetic chemistry. The undesired amide hydrolysis in Smiles rearrangement was addressed and the extra installation of N ‐chloroacetyl group in current industrial batch mode was avoided. Diclofenac sodium was obtained in 63 % isolated yield with an average yield of above 90 % for each step in a total residence time of 205 min. Abstract : An intensified six‐step continuous flow synthesis of diclofenac sodium from aniline and chloroacetic acid was developed by using a challenging and unprecedented etherification/Smiles rearrangement cascade as the key step in two types of flow reactors. The total isolated yield of diclofenac sodium was up to 63 % with an average yield of above 90 % for each step within a total residence time of 205 min.